Preparation and In Vitro and In Vivo Antitumor Effects of VEGF Targeting Micelles - Jing Chang MD; Zhe Yang BD; Junfeng Li MD; Yufen Jin MD; Yihang Gao MD; Yanwen Sun MD; Hainan Li MD; Ting Yu PhD (Technology in Cancer Research & Treatment, 2020)
Background: Doxorubicin (DOX) has antitumor effects mediated by cell viability inhibition and by inducing cellular apoptosis. However, it has limited use in clinical applications due to various factors such as hydrophobicity, dose-dependent toxicity effects on normal tissues, short cycle retention time, and low targeting ability. This study aims at enhancing hydrophilicity of DOX to restrict its toxic effects to within or around the tumor sites and also to improve its targeting ability to enhance antitumor efficiency. Methods: Micelles composed of biodegradable poly (ethylene glycol)-poly (lactic acid) copolymers (PEG-PLA) were employed to deliver DOX via a self-assembly method and were coupled to VEGF antibodies. The morphology, size, and physical stability of PEG-PLA-DOX targeting VEGF micelles (VEGF-PEG-PLA-DOX micelles) were assessed. Then, the release ability of DOX from these micelles was monitored, and their drug loading capacity was calculated. MTT assay revealed the in vitro antitumor effect of VEGF-PEG-PLA-DOX micelles. Moreover, ROS release was measured to evaluate apoptotic effects of these nanoparticle micelles. In vivo therapeutic efficiencies of VEGF-PEG-PLA-DOX micelles on a lung cancer nude mouse model was evaluated. Results: DOX-loaded micelles were obtained with a drug loading capacity of 12.2% and were monodisperse with 220 nm average diameter and a controlled in vitro DOX release for extended periods. In addition, VEGF-PEG-PLA-DOX micelles displayed a larger cell viability inhibitory effect as measured via MTT assays and greater cell apoptosis induction through in vitro ROS levels compared with PEG-PLA-DOX micelles or free DOX. Furthermore, VEGF-PEG-PLA-DOX micelles could improve in vivo antitumor effects of DOX by reducing tumor volume and weight. Conclusions: VEGF-PEG-PLA-DOX micelles displayed a larger anti-tumor effect both in in vitro A549 cells and in an in vivo lung cancer nude mouse model compared with PEG-PLA-DOX micelles or free DOX, and hence they have potential clinical applications in human lung cancer therapy.